Worktext in the contemporary world - Mendoza, Cheryl C. (Quezon City : Nieme Publishing House Co. Ltd., 2019)
"The subject Contemporary World discusses topics on geography, history, economics and political science which will help young generation learners approach contemporary world problems and issues from a geographic and historical perspective while taking into account their economic and political dimensions. An objective is presented in each lesson that will serve as the direction for the discussion of the lesson. An activity is provided at the end of each lesson to examine the comprehension and learning development of the learners. Real-life activities are also included to put the students in immediate situations allowing them to have a deeper understanding of the lessons."
Includes references.
English text.
Keywords: Globalization